PERLINDUNGAN HUKUM TERHADAP HAK-HAK PEREMPUAN DI PENGADILAN AGAMA - Mahmud Dongoran (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
In the Book of the Criminal Law Act, domestic violence is regulated in acts of persecution, morality, as well as neglect of people who should be living. However violence stipulated in Law No. 23 Year 2004 concerning the Elimination of Domestic Violence has a specific nature sehinggapersoalan domestic violence become public. The legal protection can be obtained victims of domestic violence are becoming more complex.